Analysis of supply-push strategies governing the transition to biofuel vehicles in a market-oriented renewable energy system. (1st January 2016) - Shafiei, Ehsan; Davidsdottir, Brynhildur; Leaver, Jonathan; Stefansson, Hlynur; Asgeirsson, Eyjolfur Ingi; Keith, David R.
Abstract: In this paper, the capacity expansion strategies of biofuels supply and the potential for the market development of biofuel vehicles are examined using an integrated System Dynamics model of energy and transport systems for Iceland. The biofuel markets are simulated in the context of a market-based economic system. The demand side enables an endogenous analysis of the road transport sector in which the long-term evolutions of light-duty and heavy-duty vehicle fleets are simulated through a consumer choice algorithm. Two scenarios are defined to support the fuel and infrastructure for biofuel vehicles: i) the Initial Push scenario as a tracking capacity planning strategy with an initial supply momentum, and ii) the Enthusiastic scenario as a leading capacity strategy with a continuous supply push. The results indicate that the dynamics of the bio-diesel market are not highly sensitive to the supply strategies employed. However, changing the capacity planning strategy could significantly influence the medium-term development of biogas as well as the evolution of the bio-ethanol market throughout the planning horizon until 2050. While the Initial Push scenario is less costly from a fuel supply perspective, the Enthusiastic strategy would be advantageous in terms of overall energy and transport benefits. Highlights: Biofuel markets are simulated using System Dynamics model of energy systems. Impact of two supply push policies on transition to biofuel vehicles is explored. Initial push strategy leads to higher capacity utilization with lower supply cost. Enthusiastic strategy leads to supply flexibility and higher consumer benefits.